2017
DOI: 10.1177/1477153517725775
|View full text |Cite
|
Sign up to set email alerts
|

The transition between lit and unlit sections of road and detection of driving hazards after dark

Abstract: An experiment to investigate peripheral detection performance during a driver's transition between lit and unlit sections of road was undertaken. The results suggest that when a driver moves from a lit to an unlit section of road their detection performance decreases almost immediately to that expected for the conditions of the unlit section and that there is no significant change in the subsequent 20-minute period. Tests were conducted at three luminances (0.1, 1.0 and 2.0 cd/m 2 ): while an increase from 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…A sustainable response to the problem would be to limit the glare, not to add additional ambient light. Fotios et al recently showed that a factor of 20 increase in lighting (from 0.1 to 2 cd/m 2 ) has almost no impact on reaction times [30], a further indication that it is high time to re-evaluate the evidence base for current norms.…”
Section: Discussionmentioning
confidence: 99%
“…A sustainable response to the problem would be to limit the glare, not to add additional ambient light. Fotios et al recently showed that a factor of 20 increase in lighting (from 0.1 to 2 cd/m 2 ) has almost no impact on reaction times [30], a further indication that it is high time to re-evaluate the evidence base for current norms.…”
Section: Discussionmentioning
confidence: 99%
“…Once this is possible, adding light serves no useful purpose, but only wastes energy (see e.g. [30,31]). There is room for a philosophical discussion about whether decorative architectural lighting should ever be considered sustainable, as it is not strictly required (for example to ensure public safety).…”
Section: Discussionmentioning
confidence: 99%
“…The brake-or-accelerate response used by Akashi et al 7 was a choice response. Similarly, Fotios et al 9,10 used two response buttons, a foot switch to indicate detection of a static object on the road surface and a steering wheel button to indicate detection of a vehicle ahead changing lane.…”
Section: Response Modementioning
confidence: 99%
“…In two studies, participants were recruited from two different age groups (18-30 years and 40-70 years) and found mixed results about the effect of age 9,10 : while neither study found any differences in younger and older drivers' RT to respond to the peripheral hazards, one 9 found that older drivers were worse at detecting a road surface obstacle compared to younger drivers.…”
Section: Driver Agementioning
confidence: 99%